PENGARUH METODE EKSTRAKSI TERHADAP KADAR FENOLAT TOTAL DAN AKTIVITAS ANTIOKSIDAN DAUN SALAM (Syzygium polyanthum (Wight) Walp.) - Verawati Verawati; Dedi Nofiandi; Petmawati Petmawati (Jurnal Katalisator, 2017)
The research about influence of extraction method on phenolic content and antioxidant activity of Bay leaves (Syzygium polyanthum (Wight) Walp) has been conducted.  Extraction methods used were maceration, percolation and soxhletation with ethanol 70% used as solvent extraction.  Total phenolic level were determined by using Folin Ciocalteu method whereas antioxidant activity with DPPH radical scavenging method. . The highest extractive value was obtained from percolation method at 59.8% followed by maceration at 44.4% and soxhletation 22%. The highest levels of phenolic content was obtained from percolation (103,91mg/g), followed by soxhletation (72.80 mg/g) and maceration (69.76 mg/g). The antioxidant activity was shown by IC50 values, the percolation method amounted to 49.67 µg/ml; soxhletation 49.98 µg/ml and maceration 35.05 µg/ml. Based on the results of statistical analysis SPSS 17 using one-way ANOVA known that the extraction method significantly affect phenolic content and antioxidant activity of the extract of bay leaves.